Analysis on Fracture Toughness of the L360QS/N08825 Bimetallic Composite Pipe Welded Joint. (7th October 2019) - Wang, Bin; Lan, Hongxia; Lei, Bobo
Abstract : The fracture toughness of the weld and heat-affected zone (HAZ) of the L360QS/N08825 composite pipe welded joint was evaluated by a crack tip opening displacement (CTOD) test. The fracture morphology, microstructure, and inclusion near fracture zones were observed by means of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive spectroscopy (EDS). The grain size and grain orientation of the crack propagation zone in the weld were investigated by electron back-scattered diffraction (EBSD). The results revealed that the average CTOD values of the weld and HAZ samples were relatively high, and a greater dispersion of CTOD values of the HAZ samples is due to the pop-in phenomenon in the P – V curve. The fracture surfaces of the weld and HAZ samples showed the characteristics of ductile fracture to a certain extent, whereas the fracture of the CTOD sample with the pop-in phenomenon exhibited a quasicleavage feature. High-density dislocation and a large number of inclusions were observed in the near fracture zone of the weld and HAZ samples. The stress concentration, caused by hindering the dislocation slip, was the main reason for microcrack formation. The existence of large-size grains and large-scale small-angle grain boundary in the weld implies that the cracks propagate toward the weld.